(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The transition from late adolescence to professional nursing practice involves a radical, multi-dimensional restructuring of the self (p. 1). This article examines how the rigorous nursing curriculum influences the cognitive and psychological architecture of adolescent females, moving them from self-oriented adolescent perspectives to a service-oriented professional identity (p. 1). It highlights the development of emotional intelligence, resilience, the mitigation of gender-based socialization, and the acquisition of the "nursing gaze"—a specialized clinical lens that balances deep empathy with objective scientific reasoning (p. 1).